Hubungan Pengetahuan Tentang Vaksinasi Covid-19 dengan Motivasi Remaja untuk Melakukan Vaksinasi Covid-19 - Nur Izzah; Nisyfa Amalia Mardina (Jurnal Ilmiah Kesehatan, 2024)
The Covid-19 virus is spread through contact with adolescents, who are particularly susceptible to it despite showing no symptoms. The government attempts various methods to prevent the spread of Covid-19 as the number of cases rises, one of which is through providing the COVID-19 vaccinations. This study aims to identify the relationship between youth motivation for vaccination and knowledge of the COVID-19 vaccine. This descriptive correlative study used crosssectional approach. A cluster sampling method was used and there were 105 respondents involved in this study. A Questionnaires assessing COVID-19 vaccination knowledge and COVID-19 vaccination motivation were used.The results of the study knowledge of Covid-19 vaccination obtained a p-value of 0.635 which means that there is no relationship between knowledge about COVID-19 vaccination and youth motivation to vaccinate COVID-19.